SCIENTIFIC ANALYSIS OF LOSSES IN THE INJECTION OF OIL PRODUCTS INTO A CONTAINER - Parpieva, A. J.; Maxmudov, N. A.; Hasanov, Z. S.; Eshquvvatov, SH.N. (Educational Research in Universal Sciences, 2024)
In this article, one of the problematic issues of our time, in the process of supplying combat vehicles and military equipment with oil products, which is one of the problematic issues of our time, is considered to be due to evaporation during bottling, which depends on a large number of factors (meteorological conditions, temperature at that time, physical and chemical properties of oil and oil products, etc.) will be released. Today, it is no secret that in the process of supplying military vehicles with petroleum products, they face a number of problems. Our current main task is to monitor the process of supplying military equipment with oil products, to create a program that meets the requirements of today’s digitization. That’s why we’re working on creating software.